Estimating the impact of air temperature and relative humidity change on the water quality of Lake Manzala, Egypt - Sallam, Gehan A. H.; Elsayed, E. A. (JNRD - Journal of Natural Resources and Development, 2015)
By the late eighties the problem of climate change and its possible impacts had become an issue of global concern. Climate variables play an important role in controlling the water circulation and the water quality of lakes either as freshwater reservoirs, or as brackish lagoons. In Egypt, Lake Manzala is the largest and the most productive lake of the northern coastal lakes. In this study, continuous measurement data from the Real Time Water Quality Monitoring stations in Lake Manzala was statistically analyzed to determine the regional and seasonal variations of the selected water quality parameters in relation to changes in two climate variables: air temperature and relative humidity. Simple formulas are elaborated using the DataFit software to predict the selected water quality parameters of the Lake including Power of Hydrogen (pH), Dissolved Oxygen (DO), Electrical Conductivity (EC), Total Dissolved Solids (TDS), Turbidity, and Chlorophyll as a function of air temperature and relative humidity. It was revealed that there is a measured relation between air temperature and relative humidity and the pH, DO, EC and TDS